Attribution or empathy? A study on the public opinion response framework of government social media—a qualitative comparative analysis of 21 public opinion incidents - Li, Yuan; Liu, Mingyang (Frontiers in Psychology, 2025)
This study examined the influencing factors of government social media’s public opinion response framework from the perspective of public opinion ecological governance, and provides an optimization strategy for its response. According to a qualitative comparative analysis (fsQCA) of 21 public opinion incidents, it was found that government social media tended to employ a context-responsibility framework when faced with the combined paths of high netizen attention and strong negative sentiment, as well as high media participation and elevated levels of government intervention. In contrast, a subject-emotional framework is preferred in scenarios with weak negative sentiment and incomplete initial media reporting, or when high media participation coincides with highly sensitive event types. According to these findings, issues of attribution inertia and post-event empathy in government social media responses were identified and the application of public opinion ecosystem governance principles were advocated to enhance dynamic balance, openness, and foresight, thereby optimizing capabilities in public opinion regulation, deep communication, and proactive “preventive care.”